39 - PERFORMANCE PHYSIOTHERAPIST IN CHRONIC PERIPHERAL VESTIBULAR DYSFUNCTION- CASE STUDY (Fiep Bulletin - online, 2011)
Introduction: The vestibular rehabilitation exercises to stimulate the vestibular system and maximize neuroplasticity of central nervous system, promoting physiological recovery of body balance. Objective: To analyze the effects of therapeutic exercises for vestibular rehabilitation applied in a patient with depression and chronic peripheral vestibular disease. Methods: We adopted the static balance tests (Romberg and Romberg test), dynamic equilibrium (Babinski-Weil) and coordination (index-nose, index-index test, diadochokinesia). Were also used Berg scales for assessing mobility and balance, Hamilton depression that assesses the emotional state, and the questionnaire Handicap for dizziness that aims to assess the level of disadvantage that cause dysfunction in the patient's life. The treatment was based on protocols proposed by Hawthorne (1944) and Cooksey (1946) and also included the rehabilitation protocol of HERDMAN to enhance vestibular adaptation. Results: Analysis of questionnaire HANDICAP significant change was observed in both the total score of the questionnaire, such as assessment scales physical, emotional and functional completing the improvement in quality of life of the patient. The results obtained in the Rating Scale Hamilton Depression were satisfactory, and the total score of pretreatment 36 points, and the total post-treatment 14 points, showing improvement since the lower the score, the better the emotional state and less is the incidence of harmful symptoms. In Balance Scale Berg, the score for the pre-treatment was 15 points and post-treatment 50 points and the positive result demonstrated that the treatment was effective for promoting the improvement of the steady state, since the higher the score the lower the rate imbalance. Conclusion: VR is effective in treating patients with vestibular disorders improved the vertigo, quality of life and physical well-being and mental health.
Keywords: Vestibulopathy; Vestibular Rehabilitation